Implementation of POJK 12/2023 in the Transformation of Shariah Governance and Sharia Compliance of BSN Surabaya Branch - Amran Suradi; Mugiyati (Universitas Islam Negeri (UIN) Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: This paper examines the structural transformation of the Islamic banking industry in Indonesia following the enactment of Law No. 4 of 2023 (UU P2SK) and OJK Regulation (POJK) No. 12/2023, which shifts the spin-off paradigm from a time-based to an asset-based threshold. The study examines the institutional and shariah governance challenges faced by Bank Syariah Nasional in regional markets. Research Methods: Employing a qualitative approach with a descriptive-analytical case study design, this research investigates managerial autonomy and shariah governance at the BSN Surabaya Capital Branch. Data were collected through triangulation of in-depth interviews, passive participatory observations, and documentation. Results: The findings reveal that the spin-off establishes a direct reporting line to corporate directors, yet the branch’s operational autonomy remains semi-autonomous due to its dependency on the conventional parent bank’s shared IT infrastructure. A gap also persists between formal administrative compliance and substantive shariah compliance, as daily practices remain dominated by murabahah financing using conventional interest rate benchmarks (BI-Rate). Conclusion: The transitional phase of banking spin-offs creates tensions between formal independence and functional dependency. Without strategic interventions in corporate culture and product innovation based on genuine risk-sharing, pseudo-shariah compliance may reduce customer trust and encourage switching behavior among urban Muslim consumers.